PW 1801 Being young-black-male increases the odds of suffering police non-lethal violence in brazil, according to the national health survey 2013. (November 2018) - Peres, Maria Fernanda; Levy, Renata Bertazzi; Rezende, Leandro Fórnias Machado de; Luiz, Olinda do Carmo; Grangeiro, Alexandre
Abstract : In 2015, police violence and its connections with racism gained new faces when the US protested against police killings of black men. Krieger (2015) stated that police killings of black men in the US revealed links between racism, injustice and inequity. An analysis of trends in US deaths due to legal intervention demonstrates a longstanding excess of black vs white mortality rate among 15–34 men (Krieger et al., 2016). However, the association of sex (male), age (young) and skin-color (black) with police non-lethal victimization is scarce, especially taking into account the overlapping of these social demographic characteristics (being young-black-male). Objective: To investigate the association of sex, age and skin-color with police non-lethal violence in Brazil. Method: We used data from National Health Survey Brazil 2013, a population-based survey (n=62, 202) and performed multinomial logistic regression. Result: Young and male had higher odds of being victim of violence by unknown perpetrator (VUP) (OR=1.47 and OR=1.22) and Police Violence (PV) (OR=4.13 and OR=9.44). The magnitudes of these associations were higher for PV than for UPV. Black skin colour was associated only with PV (OR=1.52). Overlaping of sociodemographic characteristics raised the odds of being a victim of violence. Odds of being victim of PV rose from 6.19, when only one risky attribute was present, to 74.93, when all three attributes were present. Conclusion: These results reinforce the idea that the historical pattern of social and racial segregation is in some extent unchanged and calls the attention of policy makers and civil society to racism in the performance of law enforcement officers. The consequences of non-lethal police violence victimization to health and well-being should be better investigated.